Implementation of digital marketing in open and distance learning universities in Indonesia - Gunawan Wiradharma; Irwan Trinugroho; Mario Aditya Prasetyo; Melisa Arisanty (Jurnal Manajemen dan Pemasaran Jasa, 2025)
In higher education, particularly within open and distance learning environments such as Universitas Terbuka, integrating digital marketing tools such as e-commerce, social media, and marketplaces is pivotal. These tools play a crucial role in enhancing brand awareness and engaging students. This study explores the strategic application of digital marketing in overcoming barriers traditionally associated with distance learning. A case study methodology was employed to provide an in-depth analysis of digital marketing practices at Universitas Terbuka, using thematic analysis to interpret data gathered from various digital marketing channels. The research identifies three primary facets of digital marketing implementation: search engine optimization, social media engagement, and video marketing. Key challenges include inadequate internet access, limited availability of technological devices, deficits in content creation skills, misalignment of human resources qualifications, and prohibitive advertising costs. This study offers insights into the effective use of digital marketing to improve accessibility and educational delivery in open universities.